LINGUISTIC AND CULTURAL CHALLENGES IN MODERN TRANSLATION (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article examines the key challenges faced by translators in contemporary practice, focusing on semantic ambiguity, cultural differences, idiomatic expressions, stylistic variations, and terminology issues. It emphasizes that translation is more than a simple transfer of words; it is a complex process requiring linguistic skill, cultural awareness, and interpretive judgment. The study highlights the importance of understanding both the source and target cultures to produce accurate and effective translations.